Maillard reaction in food allergy: Pros and cons. Issue 2 (22nd January 2018) - Gupta, Rinkesh Kumar; Gupta, Kriti; Sharma, Akanksha; Das, Mukul; Ansari, Irfan Ahmad; Dwivedi, Premendra D.
ABSTRACT: Food allergens have a notable potential to induce various health concerns in susceptible individuals. The majority of allergenic foods are usually subjected to thermal processing prior to their consumption. However, during thermal processing and long storage of foods, Maillard reaction (MR) often takes place. The MR is a non-enzymatic glycation reaction between the carbonyl group of reducing sugars and compounds having free amino groups. MR may sometimes be beneficial by damaging epitope of allergens and reducing allergenic potential, while exacerbation in allergic reactions may also occur due to changes in the motifs of epitopes or neoallergen generation. Apart from these modulations, non-enzymatic glycation can also modify the food protein(s) with various type of advance glycation end products (AGEs) such as Nϵ-(carboxymethyl-)lysine (CML), pentosidine, pyrraline, and methylglyoxal-H1 derived from MR. These Maillard products may act as immunogen by inducing the activation and proliferation of various immune cells. Literature is available to understand pathogenesis of glycation in the context of various diseases but there is hardly any review that can provide a thorough insight on the impact of glycation in food allergy. Therefore, present review explores the pathogenesis with special reference to food allergy caused by non-enzymatic glycation as well as AGEs.